1996
DOI: 10.1073/pnas.93.7.3031
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous injection of soluble antigen induces thymic and peripheral T-cells apoptosis.

Abstract: The mechanism by which tolerance is induced via systemic administration of high doses of aqueous antigen has been analyzed by using mice transgenic for a T-cell receptor specific for the influenza virus hemagglutinin (HA) peptide comprising amino acids 126-138. After intravenous injection of 750 (but not 75) ,ug of HA peptide, a state of hyporesponsiveness was rapidly induced. In the thymus, in situ apoptosis in the cortex and at the corticomedullary junction was responsible for a synchronous and massive de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
140
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(156 citation statements)
references
References 29 publications
13
140
3
Order By: Relevance
“…Thus, different mechanisms of tolerance may be prominent depending on the nature of the active tolerogenic APC population. Intravenous administration of peptide has been reported to result in a large-scale deletion of antigen-specific CD4 1 and CD8 1 naïve T cells [30,31] and also memory CD8 1 T cells [32] reminiscent of our findings here, however, induction of unresponsiveness also appears to provide some contribution to the tolerogenic effect. Traditionally, i.v.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Thus, different mechanisms of tolerance may be prominent depending on the nature of the active tolerogenic APC population. Intravenous administration of peptide has been reported to result in a large-scale deletion of antigen-specific CD4 1 and CD8 1 naïve T cells [30,31] and also memory CD8 1 T cells [32] reminiscent of our findings here, however, induction of unresponsiveness also appears to provide some contribution to the tolerogenic effect. Traditionally, i.v.…”
supporting
confidence: 81%
“…Traditionally, i.v. peptide administration has been considered to constitute ''high-dose'' tolerance [30]. In various experimental systems, high antigen loads favor induction of unresponsiveness in CD8 1 T cells, both naïve and memory, whereas lower antigen loads favor deletion or induction of regulation [33,34], and our unpublished findings.…”
supporting
confidence: 52%
“…If the liver is not a graveyard for activated cells, this raises the question of where the immune system eventually removes the large number of specific cells that arise during an immune response. The ultimate fate of activated CD8 ϩ T cells may resemble that of CD4 ϩ T cells, which undergo Ag-induced cell death in the peripheral organs where they are activated (65)(66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%
“…Different methods, such as the application of high or low doses of a specific antigen and defined routes of administration are critical factors that determine the induction of immune tolerance. The doses and concentration of the antigen are often directly correlated with the generation of active and cell-dependent regulatory mechanisms (Turley and Miller, 2010) or with the induction of anergy (Bitar and Whitacre, 1988) or even deletion of antigen-specific T cells (Critchfield et al, 1994;Liblau et al, 1996;Apostolou and von Boehmer, 2004;Judkowski et al, 2004). Likewise, immunological tolerance achieved by oral (Higgins and Weiner, 1988;Weiner, 2000;Weiner et al, 2011) and intranasal (Anderton et al, 1998;Fossati-Jimack et al, 2015) delivery of autoantigens has shown to be mediated by active suppressor mechanisms such as anti-inflammatory cytokines and regulatory cells (Chen et al, 1995;Weiner et al, 2011).…”
Section: Introductionmentioning
confidence: 99%